Banks, domestic debt, and crises: The recent Brazilian experience* - AFONSO S. BEVILAQUA; MÁRCIO G. P. GARCIA (Brazilian Journal of Political Economy, 2020)
ABSTRACT This paper examines the recent evolution of the Brazilian public domestic debt and interprets it in light of the confidence crisis literature. The analysis of the recent developments in the Brazilian public domestic debt market shows that the likelihood of a default must not be assessed only using simple summary aggregate measures of public domestic debt size and maturity, but must also consider other structural aspects. Our analysis emphasizes the two main pillars of the Brazilian public domestic debt market: home-bias and the role of the banking sector in intermediating the debt. Evidence from yields of a “perfectly” indexed bond shows that the rollover premium was very small when the devaluation occurred, and is still fairly small by October, 1999, indicating that the rollover of the public domestic debt is not, so far, a serious problem. Positive prospects for the public domestic debt market will depend, however, on the Brazilian government maintaining the current fiscal austerity program.